Decompressive craniectomy for malignant middle cerebral artery infarction at an emergency hospital in Peru - Celi, Fernando (2022)
Objective: To describe clinical, surgical and post-operative characteristics in patients with the diagnosis of malignant infarction of the middle cerebral artery who underwent decompressive craniectomy. Methods: Descriptive, retrospective case series study, performed between March 2017 and March 2020. Data from consecutive patients with the diagnosis of malignant middle cerebral artery infarction were collected. Results: Ten cases were reviewed. Eighty percent of the patients were men, the mean age was 64 years and 60% of the patients were older than 60 years. At admission, the mean Glasgow was 11 points and the mean mRS was 4. The mean time from diagnosis to surgery was 89.7 hours. The anterior cerebral artery was comprised in two cases. Hemorrhagic transformation occurred in three cases. The mean anterior-posterior diameter of the skull flap was 116 mm. The mean ICU and hospital length of stay was 14.1 and 27.5 days, respectively. Three patients died. Conclusions: Decompressive craniectomy is a life-saving procedure in an emergency hospital-setting with an acceptable in-hospital mortality rate within one-month follow-up.